2017
DOI: 10.1016/j.nlm.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila melanogaster tribbles pseudokinase is necessary for proper memory formation

Abstract: The tribbles (trbl) pseudokinases play important roles in signaling and physiology in multiple contexts, ranging from innate immunity to cancer, suggesting fundamental cellular functions for the trbls’ gene products. Despite expression of the trbl pseudokinases in the nervous systems of invertebrate and vertebrate animals, and evidence that they have a function within mouse and human dopamine neurons, there is no clear case for a function of a Trbl protein that influences behavior. Indeed, the first and only e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Subsequent work showed that mammalian Trib1 and 2 bind and degrade C/EBP to promote T cell maturation, revealing the deep conservation of the interaction between Tribs and C/EBPs [ 10 , 76 ]. While multiple genetic screens conducted over the past 20 years have linked fly Trbl to tissue differentiation in the central nervous system [ 77 , 78 , 79 ], peripheral nervous system [ 80 ], musculature [ 81 ], testes [ 82 ], ovary [ 3 ], and eye [ 83 , 84 ], the specific Trbl targets active during these tissue differentiation events remain unknown.…”
Section: Drosophila Genetic Screens Uncover a Tumor-suppressor Rolmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent work showed that mammalian Trib1 and 2 bind and degrade C/EBP to promote T cell maturation, revealing the deep conservation of the interaction between Tribs and C/EBPs [ 10 , 76 ]. While multiple genetic screens conducted over the past 20 years have linked fly Trbl to tissue differentiation in the central nervous system [ 77 , 78 , 79 ], peripheral nervous system [ 80 ], musculature [ 81 ], testes [ 82 ], ovary [ 3 ], and eye [ 83 , 84 ], the specific Trbl targets active during these tissue differentiation events remain unknown.…”
Section: Drosophila Genetic Screens Uncover a Tumor-suppressor Rolmentioning
confidence: 99%
“…Their demonstration that Trbl plays a critical role in the activation of quiescent neural stem cells during early larval development is intriguing in light of previous work done by Zars et al showing that trbl mutations result in adult behavior phenotypes, including sleep arrhythmias and short-term memory loss [ 78 , 79 ]. The Zars group showed that memory defects can be rescued by transgenic expression of Trbl in a subset of cells in the nervous system, making a compelling case that Trbl is critical for reorganization of neural circuitry necessary for subsequent adult behaviors.…”
Section: Role For Trbl In Tissue Regeneration and Stem Cell Regulamentioning
confidence: 99%